Synthesis, Characterization, Molecular Docking, In Vitro Biological Evaluation and In Vitro Cytotoxicity Study of Novel Thiazolidine-4-One Derivatives as Anti-Breast Cancer Agents - Kadhim, Zainab Y.; Alqaraghuli, Hasanain G.J.; Abd, Muna T. (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Thiazolidine-4-one is a promising class of heterocyclic compounds with interesting pharmacological and biological activities, such as anticancer and antibacterial. Therefore, many researchers have synthesized thiazolidine-4-ones and evaluated their biological potential for developing new drugs. Objective: In this study, two novel thiazolidine-4-one derivatives (T1 and T2) were synthesized and evaluated for their antibacterial activity toward Staphylococcus aureus, Escherichia coli, and Proteus mirabilis. Also, the cytotoxic activities of compounds T1 and T2 were estimated against MCF-7 (HER2+, ER+, and ER+) and MDAMB- 231 (triple-negative) human breast cancer cell lines. The chemical structures of the compounds T1 and T2 were proven using spectral techniques (FT-IR, 1HNMR, and 13CNMR) and CHN elemental analysis. Methods: The synthesis of thiazolidine-4-one compounds was performed in two steps. The first step consisted of the formation of Schiff bases S1 and S2. In the second step, the synthesized Schiff bases were reacted with thioglycolic acid to prepare thiazolidine-4-one compounds. Hemolysis assay, molecular docking, cytotoxicity activity (MTT assay), and antibacterial activity (disc diffusion assay) were studied. Results: The hemolysis study demonstrated that the hemolytic ratio of compounds T1 and T2 at (1, 2, and 3) mg/ml was less than 4%. MTT assay showed that 100 μg/ml of compounds T1 and T2 diminish the MCF-7 cell growth up to 80.05 ± 1.72 and 69.85 ± 3.26 respectively after 72hr., while the same concentration of compounds T1 and T2 reduces the MDA-MB-231 cell growth up 70.28 ± 2.31 and 57.15 ± 1.49, respectively. The inhibition zones of T1 and T2 were 12 mm at 50 mg/ml and 10 mm at 5 mg/ml in E. coli bacteria. Furthermore, a docking study was carried out to investigate the affinity and binding mode of compounds T1 and T2 towards the ERα, VEGF, and HER2 protein receptors in breast cancer cells. Data obtained from the docking study were exactly identical to that obtained from in vitro cytotoxicity assay. Conclusion: The results proved that T1 is an optimal anticancer agent toward breast cancer cells and the hemolysis study indicates the use of safety inside the body for compound T1. Synthesized compound T1 was most effective against MCF-7 cells compared to MDA-MB-231 cells and more effective than the reference drug tamoxifen in breast cell lines. The high cytotoxicity of T1 on the growth of MCF128;7 cells because T1 binds with a high degree of affinity to the estrogen and HER2 receptors, which in turn inhibits cell proliferation and induces apoptosis.
Keywords: antibacterial activity